2019
DOI: 10.1088/1367-2630/aafa39
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the electron–positron cascade regimes in high-intensity laser-matter interactions

Abstract: Strong-field quantum electrodynamics predicts electron-seeded electron-positron pair cascades when the electric field in the rest-frame of the seed electron approaches the Sauter-Schwinger field, i.e. h =Ẽ E 1 S RF . Electrons in the focus of next generation multi-PW lasers are expected to reach this threshold. We identify three distinct cascading regimes in the interaction of counter-propagating, circularly-polarised laser pulses with a thin foil by performing a comprehensive scan over the laser intensity (fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…In order to generate pair plasma by incoming laser pulses we must prepare a seed in the focal region to trigger vacuum breakdown. Here the seed can be an electron beam, a plasma or solid target, or a gamma ray (see for an example [35][36][37][38][39][40]). In general, this problem looks like the well-known air breakdown in a focused laser beam.…”
Section: Formulation Of the Problem A General Approachmentioning
confidence: 99%
“…In order to generate pair plasma by incoming laser pulses we must prepare a seed in the focal region to trigger vacuum breakdown. Here the seed can be an electron beam, a plasma or solid target, or a gamma ray (see for an example [35][36][37][38][39][40]). In general, this problem looks like the well-known air breakdown in a focused laser beam.…”
Section: Formulation Of the Problem A General Approachmentioning
confidence: 99%
“…Similar study by Luo et al [19] gives an estimate of the QED cascade saturation. Based on a semi-analytical scaling for the pair plasma density and corresponding PIC simulations, the dependency of QED cascade on initial target density has been presented by Slade-Lowther et al [20] . In fact, they have also shown that there exist three different cascade regimes with respect to initial target density in high intensity laser-thin foil interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Further simulations, however, demonstrated generation of cascades in more realistic settings, e.g. by irradiating dilute gas or electron cloud [35][36][37][38], near-critical-density plasma [39,40], or dense solid [41][42][43][44][45][46] targets. Note that in the latter case it was enough to irradiate a target from one side, since due to reflection a counterpropagating wave was formed by itself.…”
Section: Introductionmentioning
confidence: 99%